Viability of Aspergillus costaricaensis in a coffee husk carrier material and its effect on soil fertility and growth of coffee seedlings - Desak Ketut Tristiana Sukmadewi; I Gusti Bagus Udayana; I Putu Aditya Agus Saputra; Desak Ayu Diah Prawerti (Journal of Degraded and Mining Lands Management, 2023)
Planting media is an important factor affecting coffee nurseries. Farmers in Wanagiri Village have problems in coffee cultivation because they have soil with a slightly acidic pH. This affects the availability of phosphorus (P) and potassium (K) in the soil. P and potassium K solubilizing fungi can be used to increase the availability of P and K in the soil. This study aimed to analyze the viability of Aspergillus costaricaensis fungi on coffee husk carriers and the effect of A. costaricaensis biofertilizer on planting medium and the growth of Arabica coffee seedlings. The method consisted of the preparation carrier material, viability test of A. costaricaensis on coffee husk carrier, and test of the effect of A. costaricaensis on the planting medium and growth of arabica coffee seedlings. There were four fertilization treatments, i.e., P1 (organic fertilizer), P2 (100% NPK), P3 (organic fertilizer + biofertilizer), and P4 (organic fertilizer + biofertilizer + 50% NPK). Coffee husk carrier material maintained the viability of A. costaricaensis during the nine weeks of storage. The number of populations that could be maintained was log 7.67 (4.7 x 107 CFU g-1). The application of biofertilizer combined with organic fertilizers (P3) increased soil pH to 7.13, and it could potentially reduce the use of NPK fertilizer. Based on the observed growth parameters, it was shown that the treatment of biofertilizers combined with organic fertilizers increased the growth parameters of plant height and stem circumference of Arabica coffee seedlings.